Konsumsi Zat Gizi dan Dampaknya terhadap Stunting dan Underweight pada Balita Suku Tengger, Jawa Timur, Indonesia: Nutrition Consumption and Impact on Stunting and Underweight among Children in the Tengger Community, East Java, Indonesia - Muniroh, Lailatul; Rifqi, Mahmud Aditya; Indriani, Diah; Abihail, Chrysoprase Thasya; Socadevia, Annisa (Universitas Airlangga, 2025)
Background: Stunting and underweight are still nutritional problems in toddlers in the world. In 2022, the number of stunting and wasting in Indonesia is still high. There are many factors that influence undernutrition, both external and internal factors in the Tengger community. Objectives: The purpose of this study was to analyze the relationship between family characteristics, exclusive breastfeeding history, birth history, and birth attendants with the incidence of stunting and underweight in children under-5 of the Tengger Community. Methods: This study was a cross-sectional study, which samples consisted of 100 mothers of children under-5 in the traditional territory of Tengger Community, taken by the random sampling technique. Data on family characteristics, exclusive breastfeeding, birth history and birth attendants were collected using questionnaires, the nutritional status of mothers and toddlers by measuring body weight and height directly, and food consumption patterns, compiled using the SQ-FFQ sheet and a food recall. Then, the chi-square analysis was utilized to scrutinize those data. Results: No significant associations between family characteristics, breastfeeding history, birth history, and birth attendant with nutritional status of under-fives were found in W/A and H/A (p-value>0.05). Only fat intake had a significant association with W/A in under-fives (p-value=0.03) of all nutrients. Conclusions: Energy and macronutrient intake were mostly in deficit, but only fat intake was associated with underweight. Therefore, macronutrient intake needs to be increased.